Structural characterization and duplication modes of pseudogenes in plants - Flavia Mascagni (Nature Portfolio, 2021)
Abstract We identified and characterized the pseudogene complements of five plant species: four dicots (Arabidopsis thaliana, Vitis vinifera, Populus trichocarpa and Phaseolus vulgaris) and one monocot (Oryza sativa). Retroposition was considered of modest importance for pseudogene formation in all investigated species except V. vinifera, which showed an unusually high number of retro-pseudogenes in non coding genic regions. By using a pipeline for the classification of sequence duplicates in plant genomes, we compared the relative importance of whole genome, tandem, proximal, transposed and dispersed duplication modes in the pseudo and functional gene complements. Pseudogenes showed higher tendencies than functional genes to genomic dispersion. Dispersed pseudogenes were prevalently fragmented and showed high sequence divergence at flanking regions. On the contrary, those deriving from whole genome duplication were proportionally less than expected based on observations on functional loci and showed higher levels of flanking sequence conservation than dispersed pseudogenes. Pseudogenes deriving from tandem and proximal duplications were in excess compared to functional loci, probably reflecting the high evolutionary rate associated with these duplication modes in plant genomes. These data are compatible with high rates of sequence turnover at neutral sites and double strand break repairs mediated duplication mechanisms.